2017
DOI: 10.1111/mpp.12548
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine tetraphosphate modulates salicylic acid signalling and the resistance of Arabidopsis thaliana to Turnip mosaic virus

Abstract: Chloroplasts can act as key players in the perception and acclimatization of plants to incoming environmental signals. A growing body of evidence indicates that chloroplasts play a critical role in plant immunity. Chloroplast function can be regulated by the nucleotides guanosine tetraphosphate and pentaphosphate [(p)ppGpp]. In plants, (p)ppGpp levels increase in response to abiotic stress and to plant hormones which are involved in abiotic and biotic stress signalling. In this study, we analysed the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…PtRSH4a had the greatest number of ESTs indicating higher expression levels, and PtRSH4a EST abundance increased in response to a number of stresses including high levels of 2E, 4E decadienal, a volatile oxylipin associated with diatom stress signalling (Vardi et al , 2006)(Table S2). This may suggest that diatom RSH genes are involved in defence responses, as previously observed for plant RSH (van der Biezen et al , 2000; Givens et al , 2004; Kim et al , 2009; Abdelkefi et al , 2018). Furthermore, recent transcriptome experiments show that PtRSHl and PtRSH4b are induced rapidly after the onset of nitrogen starvation and in response to incubation in darkness for eight hours (Matthijs et al , 2016; Matthijs et al , 2017).…”
Section: Resultssupporting
confidence: 68%
“…PtRSH4a had the greatest number of ESTs indicating higher expression levels, and PtRSH4a EST abundance increased in response to a number of stresses including high levels of 2E, 4E decadienal, a volatile oxylipin associated with diatom stress signalling (Vardi et al , 2006)(Table S2). This may suggest that diatom RSH genes are involved in defence responses, as previously observed for plant RSH (van der Biezen et al , 2000; Givens et al , 2004; Kim et al , 2009; Abdelkefi et al , 2018). Furthermore, recent transcriptome experiments show that PtRSHl and PtRSH4b are induced rapidly after the onset of nitrogen starvation and in response to incubation in darkness for eight hours (Matthijs et al , 2016; Matthijs et al , 2017).…”
Section: Resultssupporting
confidence: 68%
“…Interestingly, HCPro, the RNA silencing suppressor of TuMV, interacts with AtCA1 (the homologue of SABP3 (SA‐binding protein 3)) to compromise the SA pathway and facilitate viral infection (Poque et al , ). Recently, it was reported that high levels of guanosine pentaphosphate or tetraphosphate ((p)ppGpp) accumulation increased susceptibility to TuMV and reduced SA content, whereas plants with lower (p)ppGpp levels were more resistant to TuMV and had increased SA content, indicating a role for the SA pathway in defence against TuMV (Abdelkefi et al , ). Our finding that transgenic NahG N. benthamiana was susceptible to TuMV, while exogenous SA enhanced N. benthamiana resistance to TuMV, demonstrates that SA participates in defence against TuMV in N. benthamiana (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, chloroplast infection by TuMV leads to physiological changes in infected plants, which may interfere with important processes such as photosynthesis. In this context, Abdelkefi et al (2018) determinate that (p)ppGpp was involved in modulation of plant immunity against TuMV using transcriptomics tools (microarray analysis). Study demonstrated that (p)ppGpp accumulation was associated with increased susceptibility to TuMV and reduced levels of the defence hormone SA.…”
Section: Potyvirus Genusmentioning
confidence: 99%